Studi Literatur: Inovasi Media Pembelajaran IPA Terkini - GH, Muliana; Ruslan, Zuhrah Adminira (Peneliti.net, 2024)
This research uses descriptive literature study research method to investigate the types of current Science learning media used and developed in the last five years. The research steps include collecting research articles related to the use of science learning media, recording the findings of the types of science learning media and theories contained in the research articles, and analyzing the findings. The data source used is secondary data, through a search on the Google Scholar page with the keyword